2017
DOI: 10.1093/mnras/stx797
|View full text |Cite
|
Sign up to set email alerts
|

Dust dynamics and evolution in H ii regions – II. Effects of dynamical coupling between dust and gas

Abstract: In this paper, we extend the study initiated in Paper I by modelling grain ensemble evolution in a dynamical model of an expanding H ii region and checking the effects of momentum transfer from dust to gas. The radiation pressure on the dust, the dust drift and the lug on the gas by the dust are all important processes that should be considered simultaneously to describe the dynamics of H ii regions. By accounting for the momentum transfer from the dust to the gas, the expansion time of the H ii region is nota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 34 publications
(43 reference statements)
1
61
0
1
Order By: Relevance
“…They concluded that if the H ii region is expanding, then the expansion velocity (V exp ) should be ≤ 1km s −1 . We note that in the series of simulations by Pavlyuchenkov et al (2013); Akimkin et al (2015Akimkin et al ( , 2017, where the parameters of RCW 120 were used as a basic model, the value of V exp was indeed found to be about 1-1.5 km s −1 . Recently, Marsh & Whitworth (2019) re-examined Herschel data using a Bayesian procedure and surprisingly found that spatial distribution of warm dust in the H ii region is consistent with the projection of a spherical shell, while colder peripheral dust has a ragged clumpy structure.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…They concluded that if the H ii region is expanding, then the expansion velocity (V exp ) should be ≤ 1km s −1 . We note that in the series of simulations by Pavlyuchenkov et al (2013); Akimkin et al (2015Akimkin et al ( , 2017, where the parameters of RCW 120 were used as a basic model, the value of V exp was indeed found to be about 1-1.5 km s −1 . Recently, Marsh & Whitworth (2019) re-examined Herschel data using a Bayesian procedure and surprisingly found that spatial distribution of warm dust in the H ii region is consistent with the projection of a spherical shell, while colder peripheral dust has a ragged clumpy structure.…”
Section: Introductionmentioning
confidence: 75%
“…Thus, the dust is well mixed with the gas in the molecular envelope of RCW 120. Simulations of Akimkin et al (2015Akimkin et al ( , 2017 show how charged dust can be expelled from an H ii region by radiation pressure, and estimate that the dust-to-gas mass ratio for the interior of an H ii region like RCW 120 can be less than 50% of the canonical value. However, the drifting dust is stopped inside the collected dense molecular envelope of the H ii region due to high gas density, and dust-to-gas mass ratio there remains near the canonical of 1:100.…”
Section: Gas As a Proxy Of Dust And Vice Versamentioning
confidence: 99%
“…As a reference for IR bubble parameters, we use results of numerical modelling, pre-computed with the MARION code and presented in the works of Pavlyuchenkov et al (2013) and Akimkin et al (2015Akimkin et al ( , 2017. To track the changes in the object physical structure, we choose three representative locations within the modelled object.…”
Section: Photo-processing In Ir Bubblesmentioning
confidence: 99%
“…With this in mind, we present a tool Shiva that combines primary destructive processes into a single model and allows calculating the dust evolution under various conditions. The Shiva tool can be used as a stand-alone feature or be included as a module into a more detailed hydrodynamical model, like the MARION model of an expanding Hii region presented in the works of Akimkin et al (2015Akimkin et al ( , 2017. Shiva shares many elements with the recently published THEMIS model (Jones et al 2017), however, in addition to processes presented in THEMIS (photo-aromatisation, sputtering), the Shiva model also accounts for photo-destruction via carbon atom loss, aromatisation by ions and electrons, and shattering processes.…”
Section: Introductionmentioning
confidence: 99%
“…where x = hν/(k B T ) and β = d log κ ν /d log ν is the opacity index characterizing the spectral properties of the dust opacity coefficient κ ν , cm 2 g −1 . To calculate κ ν we use optical properties of silicate and carbonaceous grains as in Akimkin et al (2017), but assuming power-law size distribution with the slope −3.5, grain sizes between 0.005 and 0.25µm and mass ratio 0.2:0.8 between carbonaceous and silicate dust. The corresponding spectral indices α 70/160 and α 160/250 for the cases of optically thin and thick emission is presented in Fig.…”
Section: Spectral Indicesmentioning
confidence: 99%